Penerapan Pengambilan Gambar Naturalistik Dalam Film Dokumenter “Jejak Rasa” - Shafa Najla Amira; Rinda Aunillah Sirait; Jimi Narotama Mahameruaji (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
The development of audiovisual media in the digital era provides a significant opportunity for conveying information, particularly regarding social and cultural issues. One interesting phenomenon is the acculturation of Peranakan Chinese cuisine in Indonesia, which is currently becoming less well-known among the younger generation. This study aims to represent this acculturation process through a documentary film entitled